PM.08 Metformin, Glycaemic Control and Postnatal Glucose-Tolerance-Testing in Women with Gestational Diabetes. (26th April 2013) - Stirrat, LI; Mustafa, H; Love, CDB
Abstract : Background: Metformin has been shown to be safe, effective and acceptable to women with gestational diabetes (GDM), and is recommended as the first-line pharmacological treatment for women who meet the usual criteria for insulin. Methods: We retrospectively reviewed case notes of women with GDM in the Royal Infirmary of Edinburgh (RIE) from January 2009–March 2011. Audit standards derived from local guidelines included: metformin as the first-line glucose-lowering medication in at least 90% of cases; average blood glucose readings <8.0 mmol/L over two weeks in at least 90% of cases (≥8.0 mmol/L was considered 'poor' glycaemic control); and postnatal glucose-tolerance-test (GTT) in all cases. Neonatal outcomes were observed. Results: Of the 113 pregnancies reviewed, 82.3% (93/113) of women required glucose-lowering medication. Metformin was used first-line in 94.6% of women requiring medication (88/93), and 99.6% of these continued treatment until delivery. Supplemental insulin was required in 44.3% of cases (39/88). Average blood glucose readings of <8.0 mmol/L were achieved in 93.6%, and 91.2% of cases during the second and third trimesters respectively. 70.8% of women (80/113) attended for postnatal GTT, and 25% of these (20/80) were abnormal. Macrosomia (defined as birth-weight ≥4000 g) affected 20.3% of babies. One baby required admission to the neonatal unit due to hypoglycaemia. Conclusion: In RIE, women with GDM receive appropriate medication. The quality of glycaemic control has been maintained since metformin became the first-line medication. Suboptimal attendance for postnatal GTT must be addressed to optimise the health of these women who are at risk of developing Type 2 diabetes.